The frequency and particularities functional biomechanics disorders of the infantile cerebral paralysis inter children’s of native population (the Hakass), mestizo and european of the Republic Hakasiya - I. G. Galantyuk; S. A. Solomin; I. R. Schmidt (Бюллетень сибирской медицины)
80 children’s were observed with infantile cerebral paralysis for searching frequency infantile cerebral paralysis and particularities functional biomehanic disordeved of children of native population (Hakass). The prevalence of the diagnosis ICP is in 6 time more in european group, as compared with hakas’s, and in 8 time more as compared with mestizo. On frequency of occurrence once forms ICP in all free groups on 1 place double hemiplegia; on 2 places hemiparesis form. Beside all children’s with ICP in 100 rate were discovered functional biomehanich damages, demanding corrections by methods manuall therepy.